2019
DOI: 10.3390/molecules24142615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Auxin Metabolites in Brassicaceae by Ultra-Performance Liquid Chromatography Coupled with High-Resolution Mass Spectrometry

Abstract: Auxins are signaling molecules involved in multiple stages of plant growth and development. The levels of the most important auxin, indole-3-acetic acid (IAA), are regulated by the formation of amide and ester conjugates with amino acids and sugars. In this work, IAA and IAA amide conjugates with amino acids bearing a free carboxylic group or a methyl ester group, along with some selected IAA metabolites, were studied in positive and negative electrospray ionization (ESI) modes, utilizing high-resolution mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The 4-chloroindole-3-acetic acid, an analog of IAA was detected from Microbacterium testaceum Y411 extract at m/z of 209.16 by HRMS analysis. A similar result was reported by Revelou et al. (2019) for plant IAA which found 4-chloroindole-3-acetic acid at m/z ratios 208.0167 and 210.0136.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The 4-chloroindole-3-acetic acid, an analog of IAA was detected from Microbacterium testaceum Y411 extract at m/z of 209.16 by HRMS analysis. A similar result was reported by Revelou et al. (2019) for plant IAA which found 4-chloroindole-3-acetic acid at m/z ratios 208.0167 and 210.0136.…”
Section: Discussionsupporting
confidence: 88%
“…The FTIR spectrum of the bacterial extract revealed that the detected functional groups present in auxin. Further validation through HRMS results in terms of m/z of IAA from the extracted sample was matched with the commercially available standard compound and found the IAA metabolites ( Revelou et al., 2019 ). The 4-chloroindole-3-acetic acid, an analog of IAA was detected from Microbacterium testaceum Y411 extract at m/z of 209.16 by HRMS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the colored product was an oxidation of IAA in the presence of Fe II, forming the N-hydroxy-3-indole-acetic acid product, which could be formed from any other indole analog compound and yield other indole derivated. Revelou et al (2019) demonstrated that indole-3-acetic acid (IAA) and its metabolites in plants of the Brassicaceae family belong to IAA amide conjugates with amino acids bearing a free carboxylic group or a methyl ester group. This was achieved through high-resolution mass spectrometry (HRMS) and ultraperformance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QToF-MS) methodology.…”
Section: Discussionmentioning
confidence: 99%
“…AN090126 has been demonstrated to exhibit antimicrobial activity against bacterial and fungal pathogens. In this context regarding biological activities of PGP compounds, this study highlighted the production of different kinds of interesting bioactive molecules such as germicidins (antibiotics, spore germination regulators) [ 56 ]; siderophores such as desferrioxamine E (iron uptake and transport) [ 57 ] and nocardamin (prevents plant defense against infections) [ 58 ]; many antibiotics such as CDA, prodiginines, and actinorhodin [ 59 ]; and tryptophan metabolites are related to IAA (PGP compound) [ 60 ], while kynurenic acid play a role on ethylene/auxin balance [ 61 ].…”
Section: Discussionmentioning
confidence: 99%